Improving the Bioavailability of Curcumin in Curcuma heyneana by Preparing Solid Dispersion - Sudjarwo, Sudjarwo; Bobsaid, Jihan; Windianto, Farhan Rizqi; Rizkyah, Chaerini; Shaffiqa, Nurul; Putra, Anggara Satria; Jaelani, Mochammad Iqbal; Zulfah, Yasmin; Nareswari, Andwynanda Bhadra; Fridayanti S, Septia Indah; Devitri, Nabilah Apsari; Yakub, Nikolas; Putri, Yushalluuna Bekti Pasuka; Widyowati, Retno (Berkala Ilmiah Kimia Farmasi, 2023)
Curcuma heyneana or Temu Giring contained curcumin which had anti-aging potential and was traditionally used as a body scrub. This potential comes from the active ingredient (curcumin) which could prevent premature aging with its activity as an antioxidant, inhibitor of the tyrosinase enzyme, and inhibitor of the collagenase enzyme so that it can prevent hyperpigmentation and inhibited the breakdown of collagen which can have an impact on skin aging. Oral dosage forms for anti-aging had started to be found on the market and were becoming a trend because of their convenient use. However, it is known that curcumin as an active ingredient of Temu Giring, had poor solubility and bioavailability. The bioavailability of curcumin was low when administered orally due to its low absorption and its stability which decreased significantly when the pH was above 7. This study was a literature review of national and international literature databases which aimed to determine the potential for increasing the bioavailability of curcumin using solid dispersion techniques. The results obtained indicated that making Temu Giring extract tablets containing curcumin using the solid dispersion method could increase the bioavailability of curcumin by overcoming the poor solubility, permeability, absorption and stability of curcumin. By designing the Temu Giring extract using a solid dispersion method, the curcumin could be completely dissolved and absorbed when released into the stomach. Keywords:  Curcuma heyneana, Temu Giring, Anti Aging, Tablet, Curcuminoid, Antioxidant, Solid Dispersion